Moral judgment of senior high school student in selected Philippine schools - Haertel, Alice Virginia 1920- (s.n.], 1968)
The study sought to determine the moral values of high school students in selected Filipino schools. It analyzed the roles of three variables in the formulation of moral judgments, namely, school environment; time exposure to religious instruction; and sex. The study investigates the indications of a changing pattern among the moral values held by today's youth in the Philippines